2021
DOI: 10.1186/s12939-021-01441-2
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding inequities in South Africa: Can enforcement of the WHO Code help address them? – A systematic scoping review

Abstract: Introduction Suboptimal breastfeeding rates in South Africa have been attributed to the relatively easy access that women and families have had to infant formula, in part as a result of programs to prevent maternal-to-child transmission (MTCT) of HIV. This policy may have had an undesirable spill-over effect on HIV-negative women as well. Thus, the aims of this scoping review were to: (a) describe EBF practices in South Africa, (b) determine how EBF has been affected by the WHO HIV infant feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 72 publications
0
26
2
Order By: Relevance
“…In our study, the self-reported percentage of early initiation of breastfeeding (EIBF) was high in both WLHIV and HIV-negative women (75.0%; 75.5%), and higher than previously reported in WLHIV (56.6%), HIV-negative women (61.2%) and the general population (67.3%) in South Africa [15,36], as well as globally in the general population (57.6%) as stated in a WHO global survey [37] and 58.3% in Ethiopia [38]. The EIBF rates also surpassed the WHO global target of 70% in both groups.…”
Section: Discussioncontrasting
confidence: 54%
“…In our study, the self-reported percentage of early initiation of breastfeeding (EIBF) was high in both WLHIV and HIV-negative women (75.0%; 75.5%), and higher than previously reported in WLHIV (56.6%), HIV-negative women (61.2%) and the general population (67.3%) in South Africa [15,36], as well as globally in the general population (57.6%) as stated in a WHO global survey [37] and 58.3% in Ethiopia [38]. The EIBF rates also surpassed the WHO global target of 70% in both groups.…”
Section: Discussioncontrasting
confidence: 54%
“…It was developed and used in English with all participants. Topics for the guide were developed by DV based on the authors’ systematic scoping review [ 22 ], and reviewed by RPE taking into account his experience in the field. The study was approved by Yale University’s Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic scoping review by the authors on breastfeeding inequities in South Africa [ 22 ] identified free distribution of infant formula and aggressive marketing tactics by the formula industry as negatively impacting EBF practices among both HIV-negative and positive women in South Africa. The review also highlighted that enforcement of the WHO Code is necessary but not sufficient to improve breastfeeding outcomes as other factors such as social support and quality maternity care services are needed by women antenatally and post-delivery.…”
Section: Introductionmentioning
confidence: 99%
“…This collection highlights the relevance and existing challenges in implementing structural policies needed to reduce breastfeeding inequities. Vitalis et al [ 32 ] document the experience of South Africa on how the initial WHO infant feeding recommendations for HIV positive women ended up negatively affecting breastfeeding practices also in HIV negative women and introduced major challenges to the enforcement of the International Code of Marketing of Breast-milk Substitutes (The Code). Through a scoping review Vitalis et al [ 32 ] highlighted that maternal HIV, which usually coexists with poverty became a powerful syndemic, as breastfeeding was disincentivized in the early WHO guidelines issued in the context of the then lack of access to effective antiretroviral treatments.…”
Section: Structural Policiesmentioning
confidence: 99%
“…Vitalis et al [ 32 ] document the experience of South Africa on how the initial WHO infant feeding recommendations for HIV positive women ended up negatively affecting breastfeeding practices also in HIV negative women and introduced major challenges to the enforcement of the International Code of Marketing of Breast-milk Substitutes (The Code). Through a scoping review Vitalis et al [ 32 ] highlighted that maternal HIV, which usually coexists with poverty became a powerful syndemic, as breastfeeding was disincentivized in the early WHO guidelines issued in the context of the then lack of access to effective antiretroviral treatments. Despite the enormous improvements in access to antiretrovirals as time went by in South Africa, and the issuing of new guidelines by WHO supporting breastfeeding in this new context, the legacy of the initial recommendations continues to be a formidable challenge for South African efforts at enforcing the Code.…”
Section: Structural Policiesmentioning
confidence: 99%